Answer:
b) - (x + 2)(x + 6)
c) - (x + 12)(x + 1)
c) - (x - 3)(x + 4)
f) - (x + 12)(x + 3)
Explanation:
Well to factor the given info we need to find the factors.
b)
So 6*2 = 12
6x + 2x = 8x
x*x = x^2
Factored - (x + 2)(x + 6)
c)
Well x*x = x^2
and 12*1 = 12
12x + x = 13x
Factored - (x + 12)(x + 1)
The second c)
Well x*x = x^2
-3*4 = -12
-3x + 4x = x
Factored - (x - 3)(x + 4)
f)
So x*x = x^2
12*3 = 36
12x + 3x = 15x
Factored - (x + 12)(x + 3)
Thus,
everything factored is (x + 2)(x + 6) , (x + 12)(x + 1) , (x - 3)(x + 4) ,
(x + 12)(x + 3).
Hope this helps :)